Study on the characteristics of palm oil–biodiesel–diesel fuel blend - R. El-Araby; Ashraf Amin; A.K. El Morsi; N.N. El-Ibiari; G.I. El-Diwani (Egyptian Journal of Petroleum)
Palm oil/palm oil methyl esters are blends with diesel fuel, the blends were characterized as an alternative fuels for diesel engines. Density, kinematic viscosity, and flash point were estimated according to ASTM as key fuel properties. Palm oil and palm oil biodiesel were blended with diesel. The properties of both blends were estimated. The results showed that the fuel properties of the blends were very close to that of diesel till 30% unless other characteristics are within the limits. The experimental data were correlated as a function of the volume fraction of oil/biodiesel in the blend. Different correlations were developed to predict the properties of the oil/bio-oil-diesel blends based on our experimental results. The developed correlations were validated by comparing the correlation prediction with experimental data in literature. A good agreement was found between modeled equations prediction and experimental data in literature. The developed equations can be used as a guide for determining the best blending mixture to be used for diesel engines. Keywords: Palm, Diesel, Bio-oil, Mixed oil, Viscosity, Density, Flash point